'The doctor doesn't understand Xhosa and the service user doesn't understand English' - exploring the role of security guards acting as informal interpreters in psychiatric care in South Africa - Saskia Hanft-Robert; Lindokuhle Shongwe; Qhama Cossie; Philasande Sithole; Tessa Roos; Mike Mösko; Leslie Swartz (BMC, 2024)
Abstract Introduction Assigning qualified interpreters is considered one of the most effective approaches to facilitate communication in language-discordant encounters in mental healthcare. However, particularly in settings with fewer resources, they are not always available and informal practices are often used. Objective This study aimed to investigate informal interpreting practices in mental healthcare in South Africa, focusing on security guards (SGs) serving as interpreters. Methods Guided interviews were conducted with SGs (n = 12) and mental healthcare providers (MHCPs) (n = 18) at a psychiatric hospital in South Africa. The interviews were audio recorded, transcribed verbatim and analyzed using a thematic analysis approach. Results Despite recognizing that SGs serving as interpreters is not an ideal solution to overcome language barriers and could potentially jeopardize the quality of treatment and its outcomes, MHCPs reported relying heavily on them due to the underrepresentation of South Africa's linguistic diversity among them. Given the lack of formal interpreting services, the perceived racial, linguistic and socioeconomic similarities between SGs and some service users, as well as their immediate accessibility, were described as beneficial to providing a minimal level of care (e.g. obtaining information about service users' backgrounds, getting an understanding of their symptoms, psychoeducation, explaining treatment options). Drawbacks reported are SGs being pulled away from their actual duties, experiencing emotional distress, juggling multiple sometimes conflicting roles, and the risk of incorrect interpretation, which could compromise ethical standards of care. Additionally, the complexity of power became apparent: While SGs hold little institutional power within the mental healthcare system, they become powerful figures when serving as interpreters. Conclusion It can be assumed that MHCPs will resort to informal interpreting practices as long as effective alternatives are lacking. In doing so, risks such as reduced quality of care are accepted, and the consequences and effects on those serving as interpreters are neglected, which raises concerns from an ethical point of view.